From Service Quality to Purchase Decisions in Traditional Culinary Businesses: Testing a Trust and Word of Mouth Driven Model - Isma, Andika; Nurhayani, Nurhayani; Dewantara, Hajar; Windasari, Wiwin Riski; Muflih, Betania Kertika (Quantitative Economics and Management Studies, 2025)
This study examines how service quality shapes purchase decisions in traditional culinary businesses, emphasizing the mediating roles of trust and word-of-mouth (WOM). Adopting a quantitative design that combines descriptive and explanatory approaches, we surveyed visitors to traditional foodservice establishments. Data were analyzed with PLS-SEM to test the measurement and structural models. The outer model met standard reliability and validity criteria (indicator loadings ≥ 0.60, CR ≥ 0.70, AVE ≥ 0.50). Structural results show that service quality, trust, and WOM each exert significant direct effects on purchase decisions. In addition, service quality indirectly influences purchase decisions through trust and WOM, indicating partial mediation. Overall explanatory power for purchase decisions is substantial, suggesting the model captures the key mechanisms that convert service experiences into buying choices. The findings underscore that improving frontline reliability, responsiveness, and assurance enhances customer trust, which, together with positive WOM including community and group interactions amplifies purchasing outcomes. Practically, managers of traditional culinary businesses should prioritize service-process excellence, transparent value cues, and community-based engagement programs to cultivate trust and stimulate advocacy. The study contributes by simultaneously modeling trust and WOM as mediators in a traditional culinary context and by providing actionable guidance on service strategies that sustain competitiveness in increasingly crowded foodservice markets.